The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1155/2009/363461
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Hip Dislocation in a Football Player: A Case Report

Abstract: Hip dislocations during sporting activities represent only 2%–5% of all hip dislocations. Most hip dislocations in sports can be categorised as “less complicated traumatic hip dislocations” by the Stewart-Milford classification due to the fact that minimal force is involved. The incidence of avascular necrosis of the femoral head greatly increases if the time to reduction is more than six hours. We report the case of a 38-year-old football player who suffered hip dislocation while kicking the ball with the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
(17 reference statements)
0
10
0
2
Order By: Relevance
“…Several contour lines seen at standard anteroposterior (AP) pelvic radiography aid in systematic interpretation (Fig 3) (18). Both the iliopectineal line (comprising the anterior column of the acetabulum) and the ilioischial line (comprising the posterior column) should be continuous and Hip dislocations in sporting activities are rare, representing only 2%-5% of hip dislocations, but may occur in high-velocity sports such as football and rugby (19)(20)(21). The position of the leg at the time of the trauma determines if the hip dislocates with or without fracture of the acetabulum or femoral head.…”
Section: Radiographic Anatomy Of the Hipmentioning
confidence: 99%
“…Several contour lines seen at standard anteroposterior (AP) pelvic radiography aid in systematic interpretation (Fig 3) (18). Both the iliopectineal line (comprising the anterior column of the acetabulum) and the ilioischial line (comprising the posterior column) should be continuous and Hip dislocations in sporting activities are rare, representing only 2%-5% of hip dislocations, but may occur in high-velocity sports such as football and rugby (19)(20)(21). The position of the leg at the time of the trauma determines if the hip dislocates with or without fracture of the acetabulum or femoral head.…”
Section: Radiographic Anatomy Of the Hipmentioning
confidence: 99%
“…Currently, falls from a height are the second most common cause of THDs whilst sporting injuries are a rarer cause, accounting for 2e5%. 6 THD is more common in younger patients, most frequent in men between 20 and 30 years of age. 7 The most common contemporary mechanism of injury associated with traumatic hip dislocations is road-traffic accidents.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing provided weighting, 2941 sports-related hip dislocations were estimated to have occurred over the 10-year period, representing approximately 295 injuries per year, which is higher than previously reported. 4 , 9 , 21 In 7 extreme sports, Sabesan et al 20 examined hip and knee dislocations using NEISS data from 2007 to 2012 and reported 35 hip dislocations with an estimated 742 hip dislocations during the 5-year period. While the aforementioned study is limited to hip dislocations in a select number of extreme sports, such as water skiing and wakeboarding, snowmobiling, surfing, roller skating, snowboarding, skateboarding, and snow skiing, our data represent estimates of the incidence rates for all sports-related hip dislocations in the United States.…”
Section: Discussionmentioning
confidence: 99%